Some characterizations of the properties ((LB) ̃_∞) and (〖LB〗_∞) - Thai Thuan Quang (My University, 2004)
Some characterizations of the properties ((LB) ̃_∞) and (〖LB〗_∞)
Keywords: LB property; Characterizations; Function spaces